Observation of angiographic dye leakage in ocular surface squamous neoplasia - Palme, Christoph; Wanner, Astrid; Romano, Vito; Haas, Gertrud; Kaye, Stephen; Steger, Bernhard (American journal of ophthalmology case reports, 2020)
The clinical diagnosis of ocular surface squamous neoplasia is challenging, mostly requiring excisional biopsy. Human tumor angiogenesis is characterized by abnormal vessel architecture and transvascular hyperpermeability. This case report describes features of fluorescein and indocyanine green angiography in a case of conjunctival intraepithelial neoplasia. Color photography, optical coherence tomography, fluorescein and indocyanine green angiography were performed in a patient with suspected conjunctival intraepithelial neoplasia before excisional biopsy and histologic confirmation of clinical diagnosis. Fluorescein dye showed extensive early extravascular dye leakage within the limits of the lesion. Indocyanine green dye displayed corneal terminal vessel bulbs with early leakage after 70 seconds and showed diffuse intralesional dye leakage after 7 minutes. Increased fluorescein and early indocyanine green dye leakage can be used to confirm active angiogenesis already in early stages of dysplastic ocular surface squamous neoplasia. Late leakage of indocyanine green dye may be due to chronic transvascular hyperpermeability within intrinsic tumor vessels. The leakage behaviour of intravenous dyes has the potential to serve as a diagnostic indicator of active growth in dysplastic ocular surface neoplastic lesions. •Ocular surface neoplasia allows a uniquely direct view at tumor angiogenesis.•Vascular hyperpermeability is a hallmark in malignant tumor tissues.•Angiography dye leakage may aid in the diagnosis of malignant lesions.